Analiza lokali mieszkalnych pod względem dostępności do mediów. Część 1: dostęp do wodociągów w gminie Gubin = The analysis of water supply and sewage systems in the Gubin commune. Part 1: water supply system - Fruzińska, Róża; Kostecki, Jakub; Kowalska, Kamila; Kołodziejczyk, Mariusz; Strycki, Oswald (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper we presented the results of the analysis of water supply system and sewage systems located on the area of future open pit mine Gubin-Brody. This paper presents the results for water supply system in Gubin Commune. We analyzed the current conditions and historical data.
Keywords: wodociągi; infrastruktura przesyłowa; krajobraz miejski; water supply system; water connection; water supply